Taxonomic study of the genus Ceromya Robineau-Desvoidy of Japan (Diptera: Tachinidae). - Tachi, Takuji; Shima, Hiroshi (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The Japanese species of the genus Ceromya Robineau-Desvoidy are reviewed. Ten species are recognized, eight of which are classified in three species groups: the bicolor group, flaviseta group and silacea group. Two species, C. cothurnata and C. luteola, are treated as incertae sedis. The autapomorphies of these species groups are redefined and characters illustrated: bicolor group - male genitalia: gonopod with lateral edge projected outwardly, flaviseta group - male genitalia: distiphallus in lateral view almost sclerotized, bearing small spinules ventrally, and lateral portion largely membranous, silacea group - male genitalia: distiphallus in lateral view broad, with posterolateral arm, and deeply bifurcated at apex in dorsal view; female terminalia: abdominal sterna 6-7 with minute setulae; first instar larva: labrum sharp and narrow apically. The following six species are described from Japan: C. cothurnata sp. n., C. glaucescens sp. n., C. helvola sp. n., C. kurahashii sp. n., C. luteola sp. n., and C. prominula sp. n. A key to the Japanese species is provided. Keywords Tachinidae, Siphonini, Ceromya, species group, taxonomy, Japan. Nomenclatural Acts cothurnata Tachi & Shima, 2000 (Ceromya), spec. n. glaucescens Tachi & Shima, 2000 (Ceromya), spec. n. helvola Tachi & Shima, 2000 (Ceromya), spec. n. kurahashii Tachi & Shima, 2000 (Ceromya), spec. n. luteola Tachi & Shima, 2000 (Ceromya), spec. n. prominula Tachi & Shima, 2000 (Ceromya), spec. n.